Kajian Karakteristik Kimia dan Fisika Abu Layang yang Menjadi Penentu Kekuatan Mekanik Perekat Geopolimer Berbahan Dasar Abu Layang - Diah Kartika Sari; Endang Purwanti Setyaningsih; Hamzah Fansuri; Tri Eddy Susanto (LPPM, Institut Teknologi Sepuluh Nopember, 2018)
Conversion of fly ash into geopolymers is one of the right ways to reduce the problem of coal ash waste which is hazardous and poisonous waste while its production continues to increase every year. In this study, fly ash from Pacitan power plant, Semen Gresik, Petrokimia Gresik, and Australia were used as the raw materials for making geopolymers. The geopolymers were made based on previous research. Geopolymer compressive strength that was measured at 7 days after curing was 46.71; 42.6; 42.6; 9.55 MPa, respectively. Analyses of phase composition and crystallinity, morphology and particle size and composition of fly ash constituents showed that the factor that had the strongest influence in this study was the size of fly ash particles. Fly ash with the largest particle size produces geopolymers with the lowest compressive strength. High calcium content produces a short setting time and all geopolymers that have high compressive strength are made from fly ash with a high content of Fe2O3